- Keakuratan Kode Diagnosis Penyakit Berdasarkan ICD-10 Pasien Rawat Inap Di Rumah Sakit Cakra Husada Klaten: - - Haryo Nugroho (Jurnal Permata Indonesia, 2021)
Abstract Background :. The coding should be carried out by medical record officers who have competence related to the classification and codification of diseases in accordance with the Minister of Health Regulation No. 55 of 2013 concerning the Implementation of Medical Recorder Jobs. The accuracy of the diagnosis code in the medical record file is used as the basis for making reports. Based on the results of a preliminary study conducted by researchers, the determination of the disease diagnosis code is not carried out every day in the medical record section but in the insurance section but the medical record officer still performs coding on Sundays and red dates only with the number of outpatients every day about 400 patients and outpatients. hospitalized around 50 patients with a total BOR of 46.5% in 2020. Based on this background, researchers are interested in conducting research on "The Accuracy of Disease Diagnosis Codes Based on ICD-10 Inpatients at Cakra Husada Klaten Hospital". Purpose : To determine the accuracy of the disease diagnosis code based on ICD-10 Inpatients at Cakra Husada Klaten Hospital. Methods : This study uses a descriptive research method with a quantitative approach. Results : Of the 95 inpatient diagnosis codes that have been coded by the coding officer, there are 53 accurate diagnosis codes based on ICD-10 with a percentage of 55.8% and 42 inaccurate diagnosis codes between the existing diagnosis codes in the medical record file and SIMRS with codes on ICD-10 with a percentage of 44.2%. The factors causing the inaccuracy of the disease diagnosis code based on ICD-10 are the doctor's writing is not legible, the medical language diagnosis of the disease is not known by the coding officer, the coding officer gives the code based on rote memorization, lack of accuracy from the coding officer, the coding officer still has other duties, hospital information management system error. Conclusion : The coding of inpatient diagnoses at Cakra Husada Klaten Hospital was carried out by officers with the latest education in DIII Medical Record and Health Information with coding procedures that were in accordance with standard operating procedures at the hospital. The factors that affect the accuracy of the disease code are the completeness of medical records, medical personnel, medical record personnel, and facilities. Keywords : Accuracy diagnostic code, disease code ICD-10.